2020
DOI: 10.1111/liv.14592
|View full text |Cite
|
Sign up to set email alerts
|

Identifying gaps across the cascade of care for the prevention of HBV mother‐to‐child transmission in Burkina Faso: Findings from the real world

Abstract: Background: Prevention of mother-to-child transmission (PMTCT) is a challenge for controlling the hepatitis B epidemic. In Sub-Saharan countries, pilot interventions including the screening of pregnant women for HBsAg, implementation of anti-HBV therapy and infant immunization within 24 hours of life are initiated and need to be evaluated. This pilot study aimed to describe the cascade of care for hepatitis B PMTCT in a real life situation, and to identify sociodemographic factors associated with adequate mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This package of interventions is delivered routinely in high resource settings, but infrequently across Africa. Integration of activities into existing HIV prevention of mother-to-child transmission and Expanded Programme on Immunisation infra structure distinguishes our approach from a recently published feasibility study of an antenatal HBV programme in Burkina Faso, 8 and our study yielded a higher uptake of HBV screening at the first antenatal visit. We longitudinally followed up HBV-infected women and their exposed infants to document adherence to the care cascade, side-effects of birth-dose vaccine and tenofovir disoproxil fumarate, and the incidence of mother-to-child transmission.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This package of interventions is delivered routinely in high resource settings, but infrequently across Africa. Integration of activities into existing HIV prevention of mother-to-child transmission and Expanded Programme on Immunisation infra structure distinguishes our approach from a recently published feasibility study of an antenatal HBV programme in Burkina Faso, 8 and our study yielded a higher uptake of HBV screening at the first antenatal visit. We longitudinally followed up HBV-infected women and their exposed infants to document adherence to the care cascade, side-effects of birth-dose vaccine and tenofovir disoproxil fumarate, and the incidence of mother-to-child transmission.…”
Section: Discussionmentioning
confidence: 95%
“…However, the feasibility of providing antiviral prophylaxis for HBV mono-infected pregnant women in low-resource settings in sub-Saharan Africa is not well established. Only one study 8 was done in Burkina Faso, which attempted to address this issue; this study found large gaps in HBV prevention of mother-to-child transmission and did not attempt to leverage the existing HIV prevention of motherto-child transmission programme.…”
Section: Introductionmentioning
confidence: 99%
“…The major risk of failure of this treatment is the presence of a high viral load in the pregnant woman [5][6][7][8][9][10]. Prevalence of HBs antigen positive (HBsAg+) pregnant women ranges from 3.2% in Eritrea, 4.8% in Burkina Faso to 11% in Republic of South Soudan [11,12]. Among them, about 7.5% in Burkina Faso [11], 5.6% in the Democratic Republic of the Congo [7], and 5.2% in Mozambique [13] have an elevated viral load.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of HBs antigen positive (HBsAg+) pregnant women ranges from 3.2% in Eritrea, 4.8% in Burkina Faso to 11% in Republic of South Soudan [11,12]. Among them, about 7.5% in Burkina Faso [11], 5.6% in the Democratic Republic of the Congo [7], and 5.2% in Mozambique [13] have an elevated viral load. However, administrating the birth dose of HBV vaccine is frequently logistically difficult, making the HBV MTCT prevention program suboptimal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation